ECHINACEA AND VALERIANA EXTRACTION IN DIFFERENT SOLUTIONS BY ACOUSTIC INFLUENCE - Dmitry Nikolaevich Vedernikov; Elizaveta Mikhailovna Petrova; Darya Viktorovna Zarembo (Химия растительного сырья, 2022)
The article presents the results of studying the influence of a weak vibration effect on the extraction of plant raw materials, obtained as a continuation of the previous study [1].The article describes the option of intensification extraction process from the Echinacea purpurea L. and Valeriana officinalis L. The influence of acoustic action (tensile-pulse modulation) on an increase in the yield of extractive substances when using water, 40% and 70% ethanol is discussed. The influence of the frequency and amplitude of the action during the generation of a signal in the form of a meander has been studied. Solvents are selected taking into account the use in existing pharmaceutical factories. The extraction results were evaluated by the solid residue, the optical density of the solution after extraction of Echinacea and by GLC and GLC-MS after extraction of Valeriana. The greatest effect is achieved when using water. The explanation of the results is based on the effect of vibration on the rotation of solvent clusters. Cluster sizes decrease from water to 70% ethanol.